Technology Innovation for Sustainability in the Building Construction Industry: An Analysis of Patents from the Yangtze River Delta, China - Lingyue Li; Lie Wang; Xiaohu Zhang (Buildings, 2022)
Advances in technology provides the potential to innovate sustainability in the building construction industry. Drawing on the literature and expert reviews, this research discloses the potential of 14 specific technologies in waste minimisation, energy saving, and efficiency improvement for sustainable building construction and develops a conceptual framework engaging the building life cycle (the planning, construction, use and operation, and demolition phases) and the actors for assessing technological innovation at a local level. This framework is used to identify how technologies were innovated for sustainable building construction through the selected 3017 patent invention applications from the Yangtze River Delta (YRD), one of the fastest urbanising areas and the largest market for the building industry in China. Findings unveiled that innovation is uneven amongst the 14 technologies and the degree of mixing was relatively low in the YRD. The contribution of the technological innovation to sustainability is mainly actualised through efficiency improvements in building construction (2265) and through directly reducing waste (1094) and energy consumption (642). Some general-purpose technologies (e.g., blockchain, cloud computing), which assume to fundamentally innovate the industry, are mostly absent with less than 10 records each, leaving the potential for future adaptive technological innovation. Furthermore, state-owned enterprises as the main sources of patent inventions amongst applicants in the YRD may suggest the dissimilar path of China towards technology innovation compared to its Anglo-American counterparts.